Monetary policy rules under bounded rationality - Michael Dobrew; Rafael Gerke; Daniel Kienzler; Alexander Schwemmer (Deutsche Bundesbank, 2023)
We study the welfare performance of various simple monetary policy rules under bounded rationality (BR) along the lines of Gabaix (2020) in a New Keynesian model with sticky wages and an effective lower bound (ELB) on interest rates. Policy strategies with a strong history dependence lose their advantage over inflation targeting in mitigating a demand-driven recessions when interest rates are constrained by the ELB. For supply shocks, inflation t argeting o utperforms h istory-dependent r ules f or a s ufficiently high degree of BR. An exponential average inflation targeting rule, which features a variable degree of history dependence, performs remarkably well, independent of the degree of BR.
Keywords: E20; E24; E31; E32; E52; 330; Bounded Rationality; Sticky Wages; Monetary Policy Strategies; Zero LowerBound